A real-world safety surveillance study of aducanumab through the FDA adverse event reporting system - Huang, Jingjing; Long, Xiaohong; Chen, Chunyong (Frontiers in Pharmacology, 2025)
BackgroundAlzheimer’s disease poses a major public health challenge, with aducanumab’s approval in 2021 as the first disease-modifying therapy raising important safety considerations. This study analyzed the Food Drug Administration Adverse Event Reporting System (FAERS) database to evaluate aducanumab’s real-world safety profile and identify potential risk factors.MethodsWe conducted a comprehensive pharmacovigilance study using the FAERS database from January 2004 to June 2024, analyzing 510 aducanumab-associated reports from integrated databases containing over 18 million demographic records and 66 million drug records. Safety signals were evaluated using four complementary disproportionality methods: Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-item Gamma Poisson Shrinker (MGPS). Analyses were stratified by age and sex, with adverse events examined at both System Organ Class (SOC) and Preferred Term (PT) levels using SAS 9.4.ResultsAmong 510 aducanumab-associated adverse event reports, predominantly from elderly patients (55.49% aged ≥65 years), nervous system disorders were the most frequent (53.24%, n = 583). Amyloid related imaging abnormality-oedema/effusion (ARIA-E) and Amyloid related imaging abnormality-microhaemorrhages and haemosiderin deposits (ARIA-H) emerged as the most significant safety signals (ROR: 53,538.3 and 38,187.9, respectively). Sex-stratified analysis showed comparable safety profiles between males and females, with ARIA-E related events, ARIA-H related events, maintaining strong signals across all age groups, particularly in patients ≥75 years. The median time to adverse event onset was 146.0 days (IQR: 80.0–195.0). Temporal analysis revealed increasing signal strength for ARIA-related events from 2004–2024, with notable intensification during 2022–2023.ConclusionOur real-world analysis identified ARIA-related events as the primary safety concern for aducanumab, typically occurring within 146 days of treatment initiation, with comparable safety profiles across sex but heightened risks in patients ≥75 years. These findings support aducanumab’s viability as a therapeutic option while emphasizing the critical importance of rigorous monitoring protocols, particularly for ARIA events during the first year of treatment.